Civil law notaries according to Sharia compliance in property financing contracts - Maulin, Mery; Athoillah, Mohamad Anton; Effendi, Deden; Hardinata, Cosvi (Technium Social Sciences Journal, 2021)
The purpose of this study is to determine the competencies possessed by civil law notaries following sharia compliance, with the hope of maximizing the implementation of mediating the mutanaqisah musharakah contract between customers and Islamic banks in Indonesia so that it can be carried out effectively and efficiently without any mismatch of sharia values. Where these parties are required to carry out the functions of property. This study uses a qualitative research method by analyzing documents, including examining journal article sources, book sources, legal sources from written legal documents, and conducting interviews with informants focused on finding information and understanding about sharia compliance regarding musharakah mutanaqishah based on relevant documents and by the specified research topic. The findings of this research are that Civil law notaries must have absolute competence and relative competence (subjective) in carrying out their profession. To not become a part or partner of a conventional bank, because it is indicated that you will mix Islamic values with conventional values, then you must have the ability to understand and have insight into sharia law so that you can convey information that does not cause misunderstandings about Islamic financing contracts, especially musharakah mutanaqishah. The competence of civil law notaries who have the authority to make sharia banking deeds is civil law notaries who carry out their positions and professional jobs by civil law notaries and meet the provisions of sharia compliance.